Malignant epithelioid hemangioendothelioma of liver - Sahai, Puja; Joshi, Prashant; Sharma, Daya Nand; Haresh, Kunhi Parambath; Chandrashekhara, SH; Julka, Pramod Kumar; Safaya, Rajni; Rath, Goura Kishor (Translational Gastrointestinal Cancer, 2012)
Hepatic epithelioid hemangioendothelioma (HEH) is a rare neoplasm arising from the vascular endothelial cells of liver. It commonly affects middle-aged females and entails a low to intermediate malignant potential between hepatic hemangioma and hepatic angiosarcoma. All the current treatment recommendations are based on evidence from limited retrospective clinical series. Because of the rarity of this tumour and unpredictable natural history, a direct comparison between various therapeutic modalities has not been possible. Herein, clinical presentation of HEH in a woman is described. The pertinent pathological and radiological details along with the management strategy are discussed.